Increase in bone mineral density of patients with spondyloarthropathy treated with anti-tumour necrosis factor α. Issue 4 (1st April 2003) - Allali, F; Breban, M; Porcher, R; Maillefert, J F; Dougados, M; Roux, C
Abstract : Objective: To determine the changes in bone mineral density (BMD) in patients with spondyloarthropathy (SpA) treated with infliximab. Patients and methods: 29 patients (six women; 23 men) aged 22–68 years, with persistently active SpA despite a high dose of non-steroidal anti-inflammatory drug and/or treatment with methotrexate or sulfasalazine, were studied. Median duration of disease was 13 years (range 3–30). Twenty five patients were treated with 5 mg/kg and four with 3 mg/kg of infliximab at weeks 0, 2, 6 and then received either no infusion (n=3), or additional infusion of infliximab every other month (n=6), and the remainder received one infusion only in the case of a relapse. Lumbar and femoral BMD was measured by dual energy x ray absorptiometry at baseline and six months later. Serum osteocalcin and urinary deoxypyridinoline were measured in 19 patients at weeks 0, 2, 24, and in 13 patients at all visits. Results: In six months there was a significant increase in BMD at the spine (3.6%, p=0.001), total hip (2.2%, p=0.0012), and trochanter (2.3%, p=0.0012). A trend for increase (1.1%) was observed at the femoral neck. There was an increase in osteocalcin between baseline and week 6 (third infusion)—median 1.45 μg/l (p=0.013). No change in marker of bone resorption was observed at the same time. There was no change in biochemical markers between baseline and final visits. There was a trend for a correlation between the decrease at six months in erythrocyte sedimentation rate, and lumbar spine BMD change ( r s =−0.35, p=0.06). Conclusion: These data suggest that a benefit of anti-tumour necrosis factor α therapy on BMD in patients with SpA may be through an uncoupling effect on bone cells.